A method for preparing solar cells by modifying perovskite thin films with 1,4-dithiane and its derivatives

By modifying the defects of the perovskite film with 1,4-dithianes and their derivatives, the problems of inefficiency and poor stability caused by defects in perovskite solar cells are solved, and a significant improvement in photoelectric conversion efficiency and stability are achieved.

CN116056475BActive Publication Date: 2025-04-01DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310151851.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-22
Publication Date
2025-04-01
Estimated Expiration
2043-02-22

AI Technical Summary

Technical Problem

The defects present in perovskite solar cells lead to inefficiency and poor stability, limiting their large-scale applications.

Method used

The defects of the perovskite film are modified by 1,4-dithianes and their derivatives, and non-radiative recombination is inhibited through passivation and the charge stability is improved.

Benefits of technology

It effectively improves the photoelectric conversion efficiency and stability of perovskite solar cells, significantly improves the filling factor, and the efficiency reaches more than 24%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116056475B_ABST
    Figure CN116056475B_ABST
Patent Text Reader

Abstract

A method for preparing solar cells by modifying perovskite films with 1,4-dithiane and its derivatives, which belongs to the technical field of perovskite solar cells. The method introduces an organic substance 1,4-dithiane and its derivatives as a perovskite layer modification material, and prepares a modified perovskite layer by adding 1,4-dithiane and its derivatives into a perovskite precursor solution and spin-coating a solution of 1,4-dithiane and its derivatives on a doped perovskite light-absorbing layer. After 1,4-dithiane and its derivatives are introduced into the perovskite layer, lead site defects can be effectively passivated, non-radiative recombination in the charge transfer process can be limited, and the hydrophobicity of 1,4-dithiane and its derivatives can be used to stabilize the perovskite phase. This method can effectively reduce the battery efficiency loss caused by perovskite defects, and obtain a stable and efficient perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite solar cells and relates to a perovskite modification method and a preparation process of a perovskite solar cell. Background Art

[0002] As a new generation of photovoltaic technology, perovskite solar cells have attracted widespread attention due to their excellent photoelectric performance and low cost. Since its discovery in 2009, the efficiency of perovskite solar cells has increased from 3.8% to 25.7%, showing an efficiency comparable to that of crystalline silicon solar cells. The development prospects are very promising and have gradually become the research direction of many researchers. Despite this, further improvement of efficiency and battery stability are still the biggest problems facing this field. Among them, the factor restricting the efficiency and stability of perovskites is the existence of defects in perovskites. Defects on the surface and bulk of perovskites will become non-radiative recombination centers, causing non-radiative recombination of charges and affecting the photoelectric conversion efficiency of solar cells. At the same time, defects provide binding sites for moisture and oxygen in the environment, destroying the stability of the perovskite phase, thereby reducing the service life of the battery and restricting the large-scale application of perovskite solar cells. One of the important methods to solve perovskite crystal defects is to passivate the surface and bulk defects of perovskites. There are a large number of charge traps on the surface or grain boundaries of perovskite films. These traps are mainly composed of uncoordinated ions Pb on the crystal surface. 2+ , I - Passivation refers to the use of certain chemicals to react with defects on the surface or grain boundaries to inactivate their electronic or chemical activity and fill the I - The vacancies generated by migration inhibit the non-radiative recombination of charges at the defects, thereby improving the photoelectric efficiency and stability of the battery. Summary of the invention

[0003] In order to solve the problems existing in the prior art, the present invention provides a surface and bulk modified perovskite layer and a method for preparing a solar cell, the purpose of which is to use 1,4-dithiane and its derivatives to passivate the defects of the perovskite film and inhibit non-radiative recombination. Using them in perovskite solar cells can effectively improve the photoelectric performance and stability of the device.

[0004] The technical solution adopted by the present invention is:

[0005] A method for modifying a perovskite layer with 1,4-dithiane and its derivatives, wherein the perovskite layer is a layer of a perovskite solar cell, and the perovskite layer is Cs x (FA,MA) 1-x PbI 3-y Br y Or all-inorganic perovskite CsPbI z Br 3-zOne of the following, in which FA is CH(NH2)2 + , MA is CH3NH3 + , 0≤x<0.1, 0≤y<0.6, 0≤z≤3;

[0006] This method uses 1,4-dithiane modifiers to passivate lead site defects on the surface and bulk of perovskite, forming passivation on the surface and grain boundaries of the perovskite to obtain a surface and bulk modified perovskite layer:

[0007] The specific steps of this method are:

[0008] (1) adding a 1,4-dithiane modifier to a perovskite precursor solution, and spin coating and annealing the precursor solution to form a doped perovskite layer; the ratio of the 1,4-dithiane modifier to the perovskite precursor solution is (0.1-10) mg: 1 mL;

[0009] The general structural formula of the 1,4-dithiane modification is:

[0010]

[0011] Wherein: R1, R2, R3, R4 are hydrogen, C1-C 18 Any one of an alkyl chain, hydroxyl, methoxyl, amine, or thiol;

[0012] (2) Spin coating a 1,4-dithiane modification solution on the doped perovskite layer and placing it at 20°C-100°C for 10-15 minutes to obtain a modified perovskite layer; the concentration of the 1,4-dithiane modification solution is 1-5 mg mL -1 , the solvent used in the solution is isopropanol, ethanol or ethyl acetate;

[0013] The perovskite layer is Cs x (FA,MA) 1-x PbI 3-y Br y When the molar ratio of lead iodide: methylammonium iodide: lead bromide: methylammonium bromide: cesium iodide in the precursor solution is 1-1.5:1-1.5:0-0.5:0-0.5:0-0.1;

[0014] The perovskite layer is CsPbI z Br 3-z When the molar ratio of lead iodide: lead bromide: cesium iodide: cesium bromide in the precursor solution is 0-3:0-3:0-3:0-3, and the ratio of lead iodide to lead bromide cannot be zero at the same time, and the ratio of cesium iodide to cesium bromide cannot be zero at the same time.

[0015] A method for preparing a solar cell by modifying a perovskite film with 1,4-dithiane and its derivatives. The perovskite solar cell comprises a transparent conductive substrate, an electron transport layer, a modified perovskite layer, a hole transport layer, and a metal electrode. The method comprises the following specific steps:

[0016] (1) ultrasonically cleaning the transparent conductive substrate in different solvents;

[0017] (2) after step (1), preparing an electron transport layer on the transparent conductive substrate by chemical bath deposition or thermal spraying; the electron transport layer is tin dioxide or titanium dioxide;

[0018] (3) subjecting a transparent conductive substrate having an electron transport layer to an ultraviolet ozone surface treatment to obtain a modified perovskite layer using the above method;

[0019] (4) preparing a hole transport layer solution on the modified perovskite layer by spin coating;

[0020] The hole transport layer solution comprises a hole transport material, an additive, and an organic solvent, wherein the hole transport material is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene; the additive is bis(trifluoromethane)sulfonyl imide, 4-tert-butylpyridine and tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt tris(1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide salt); and the organic solvent is chlorobenzene or acetonitrile;

[0021] (5) A metal electrode is deposited onto the hole transport layer by vacuum evaporation.

[0022] Furthermore, the structures of the 1,4-dithiane modifiers that can be used are as follows:

[0023]

[0024] Furthermore, the specific steps of the method for modifying the perovskite layer are as follows: 0.1-10 mg of 1,4-dithiane or its derivatives are added to 1 mL of the perovskite precursor solution, and the precursor solution is spin-coated and annealed to form a doped perovskite layer. -1 The 1,4-dithiane or its derivative solution is spin-coated on the doped perovskite layer and placed at 20°C-100°C for 10-15 minutes to obtain the modified perovskite layer; the solvent used in the 1,4-dithiane or its derivative solution is isopropanol, ethanol or ethyl acetate.

[0025] Furthermore, the specific steps of the method for preparing a perovskite solar cell are as follows:

[0026] (1) ultrasonically cleaning the transparent conductive substrate in different solvents, followed by ultraviolet ozone surface cleaning;

[0027] (2) after step (1), preparing an electron transport layer on the transparent conductive substrate by chemical bath deposition or thermal spraying; the electron transport layer is tin dioxide or titanium dioxide;

[0028] (3) subjecting the conductive substrate coated with the electron transport layer to ultraviolet ozone surface treatment, and spin coating a perovskite precursor solution containing 1,4-dithiane or its derivatives to prepare a perovskite film;

[0029] The perovskite film is Cs x (FA,MA) 1-x PbI 3-y Br y Or all-inorganic perovskite CsPbI z Br 3-z One of the following, in which FA is CH(NH2)2 + , MA is CH3NH3 + , 0≤x<0.1, 0≤y<0.6, 0≤z≤3; and add 0.1-10mg mL -1 1,4-dithiane or its derivatives;

[0030] (4) spin coating a solution of 1,4-dithiane or its derivatives on the doped perovskite layer prepared in step (3) to perform surface passivation treatment;

[0031] (5) preparing a hole transport layer solution on the perovskite film passivated in step (4) by spin coating;

[0032] The hole transport layer solution comprises a hole transport material, an additive, and an organic solvent, wherein the hole transport material is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene; the additive is bis(trifluoromethane)sulfonyl imide, 4-tert-butylpyridine and tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridine]cobalt tris(1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide salt); and the organic solvent is chlorobenzene or acetonitrile;

[0033] (6) Depositing a metal electrode onto the hole transport layer by vacuum evaporation.

[0034] The perovskite layer is Cs x (FA,MA) 1-x PbI 3-y Br y When the precursor solution is used, the molar ratio of lead iodide: methylammonium iodide: lead bromide: methylammonium bromide: cesium iodide is 1-1.5:1-1.5:0-0.2:0-0.2:0-0.1.

[0035] The perovskite layer is CsPbI z Br 3-z When the precursor solution contains lead iodide: lead bromide: cesium iodide: cesium bromide, the molar ratio is 0-3:0-3:0-3:0-3.

[0036] The method for modifying perovskite of the present invention is used to prepare perovskite solar cells.

[0037] The film in step (3) is Cs x (FA,MA) 1-x PbI 3-y Br y Or all-inorganic perovskite CsPbI z Br 3-z One of the following; wherein FA is CH(NH2)2 + , MA is CH3NH3 + , x is any value between 0 and 0.1, y is any value between 0 and 0.6, and z is any value between 0 and 3;

[0038] (a) When the perovskite film is Cs x (FA,MA) 1-x PbI 3-y Br y The precursor solution preparation method is to dissolve lead iodide PbI2, formamidinium iodide FAI, lead bromide PbBr2, methyl ammonium bromide MABr, cesium iodide CsI and 1,4-dithiane or its derivatives in an organic solvent at a specific molar ratio, and stir at 60°C;

[0039] (b) When the perovskite film is CsPbI z Br 3-z The precursor solution preparation method is to dissolve lead iodide PbI2, lead bromide PbBr2, cesium iodide CsI, cesium bromide CsBr and 1,4-dithiane or its derivatives in a specific molar ratio in an organic solvent, and stir at 60°C; wherein the organic solvent is a mixed solvent of N,N-dimethylformamide DMF and dimethyl sulfoxide DMSO in a certain volume ratio.

[0040] In step (5), the hole transport layer solution comprises a hole transport material, an additive, and an organic solvent, wherein the hole transport material is Spiro-OMeTAD; the additive is LiTFSI, 4-tert-butylpyridine, and FK209 Co(III)-TFSI; and the organic solvent is chlorobenzene and acetonitrile;

[0041] The metal electrode described in step (6) is one of gold and silver.

[0042] The beneficial effects of the present invention are as follows: 1,4-dithiane and its derivatives can effectively passivate lead site defects on the surface and bulk of perovskite, limit unfavorable non-radiative recombination of carriers, and utilize the hydrophobicity of 1,4-dithiane and its derivatives to stabilize the perovskite phase to improve the efficiency and stability of the device. Compared with unmodified devices, the photoelectric conversion efficiency of perovskite solar cells based on 1,4-dithiane and its derivatives can reach more than 24%. The mixing of 1,4-dithiane and its derivatives into the precursor solution and the spin coating process are simple and easy to prepare, providing a way for the commercial application of perovskite solar cells. This method can effectively reduce the non-radiative recombination loss of the battery, obtain stable and efficient perovskite solar cells, and provide a feasible strategy for the development of perovskite solar cells.

[0043] The fill factor (FF) is mainly determined by the series resistance, bypass resistance and pn junction characteristics: when the series resistance increases, the bypass resistance decreases, and there are defects and impurities in the pn junction, the FF will become smaller. When the FF becomes smaller, the energy conversion efficiency of the perovskite solar cell will decrease linearly; in this application, not only the open circuit voltage (Voc) and short circuit current density (Jsc) are slightly improved, but also the fill factor (FF) is significantly improved by more than 3.5%, and the maximum improvement reaches 6.8%; so that the fill factor can reach more than 80%, and the highest reaches 83.59%; because the passivation effect of 1,4-dithiane and its derivatives reduces defects and increases the fill factor, the efficiency of the battery is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 JV curve of organic-inorganic hybrid FAPbI3 perovskite solar cell based on 1,4-dithiane modification technology.

[0045] Figure 2 JV curve of organic-inorganic hybrid CsFAMA perovskite solar cell based on 1,4-dithiane modification technology.

[0046] Figure 3 JV curve of pure inorganic CsPbI2Br perovskite solar cell based on 1,4-dithiane modification technology.

[0047] Figure 4 JV curve of organic-inorganic hybrid FAPbI3 perovskite solar cell based on 1,4-disulfide-2,5-diol modification technology.

[0048] Figure 5 This is the Pb 4f orbital X-ray photoelectron spectrum of the organic-inorganic hybrid FAPbI3 perovskite film based on 1,4-dithiane modification technology.

[0049] Figure 6This is the steady-state fluorescence spectrum of the organic-inorganic hybrid FAPbI3 perovskite solar cell based on 1,4-dithiane modification technology. DETAILED DESCRIPTION

[0050] The following specific embodiments and drawings are used to describe the preparation and application of the present invention in detail. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0051] Example 1

[0052] Organic-inorganic FAPbI3 perovskite solar cell using 1,4-dithiane (DT) as a modified layer and preparation method thereof:

[0053] The structure of a perovskite solar cell is:

[0054] FTO / SnO2 / FAPbI3-DT / DT / Spiro-OMeTAD / Au.

[0055] The preparation process of the above perovskite solar cell is:

[0056] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.

[0057] (2) Using a water bath deposition method, the treated FTO was immersed in a water bath deposition solution. The water bath deposition solution was a mixed solution of 50 mL deionized water, 625 μL 37.5% hydrochloric acid, 12.5 μL thioglycolic acid, 625 mg urea and 137.5 mg stannous chloride dihydrate. The water bath deposition solution was heated to 90°C for 4 hours, and then the FTO was washed with deionized water and placed on a heating plate at 170°C for 1 hour.

[0058] (3) Lead iodide PbI2, formamidinium iodide FAI, lead bromide PbBr2, methyl ammonium bromide MABr, and cesium iodide CsI were dissolved in a 1 mL mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio 8:1) at a molar ratio of 1:1:0:0:0, and then 1 mg of DT powder was added and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 2000 rpm for 10 s and 6000 rpm for 30 s. 20 s before the end of the program, 100 μL of chlorobenzene was dropped on the substrate and annealed at 100°C for 1 h.

[0059] The structure of the modified material (DT) used is:

[0060]

[0061] (4) Then 60 μL of 1 mg mL -1 The DT solution was dropped onto the perovskite film by spin coating process at 4000 rpm for 20 s.

[0062] (5) A hole transport layer solution (90 mg Spiro-OMeTAD, 39.5 μL tert-butylpyridine, 23 μL LiTFSI, 10 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film by spin coating, with the rotation speed controlled at 3000 rpm and the spin coating time at 30 s.

[0063] Finally, 100 nm of Au was deposited on the device film by vacuum evaporation.

[0064] Comparative Example 1

[0065] Preparation method of FAPbI3 unmodified perovskite solar cells:

[0066] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.

[0067] (2) Using a water bath deposition method, the treated FTO was immersed in a water bath deposition solution. The water bath deposition solution was a mixed solution of 50 mL deionized water, 625 μL 37.5% hydrochloric acid, 12.5 μL thioglycolic acid, 625 mg urea and 137.5 mg stannous chloride dihydrate. The water bath deposition solution was heated to 90°C for 4 hours, and then the FTO was washed with deionized water and placed on a heating plate at 170°C for 1 hour.

[0068] (3) Lead iodide PbI2, formamidinium iodide FAI, lead bromide PbBr2, methyl ammonium bromide MABr, and cesium iodide CsI were dissolved in a 1 mL mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio 8:1) at a molar ratio of 1:1:0:0:0, and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 2000 rpm for 10 s and 6000 rpm for 30 s. 20 s before the end of the program, 100 μL of chlorobenzene was dropped on the substrate and annealed at 100°C for 1 h.

[0069] (4) A hole transport layer solution (90 mg Spiro-OMeTAD, 39.5 μL tert-butylpyridine, 23 μL LiTFSI, 10 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film by spin coating, with the rotation speed controlled at 3000 rpm and the spin coating time at 30 s.

[0070] Finally, 100 nm of Au was deposited on the device film by vacuum evaporation.

[0071] Figure 1 The JV curves of the unmodified perovskite solar cell based on DT modification are compared. The PCE of the unmodified perovskite solar cell in Comparative Example 1 is 22.07%, where V oc 1.17V, J sc 24.57mAcm -2 , FF is 76.81%, and the photoelectric conversion efficiency PCE of the perovskite solar cell based on DT modification technology in Example 1 is 24.95%, wherein V oc 1.20V, J sc 24.97 mA cm -2 , FF is 83.59%; the PCE of the perovskite solar cells before and after modification increased from 22.07% to 24.95%, an overall increase of 11.4%, and the photoelectric conversion efficiency after modification exceeded 24%.

[0072] Example 2

[0073] Organic-inorganic CsFAMA perovskite solar cell using 1,4-dithiane (DT) as a modified layer and preparation method thereof: The structure of the perovskite solar cell is:

[0074] FTO / SnO2 / CsFAMA-Perovskite-DT / DT / Spiro-OMeTAD / Au.

[0075] The preparation process of the above perovskite solar cell is as follows:

[0076] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.

[0077] (2) Using a water bath deposition method, the treated FTO was immersed in a water bath deposition solution. The water bath deposition solution was a mixed solution of 50 mL deionized water, 625 μL 37.5% hydrochloric acid, 12.5 μL thioglycolic acid, 625 mg urea and 137.5 mg stannous chloride dihydrate. The water bath deposition solution was heated to 90°C for 4 hours, and then the FTO was washed with deionized water and placed on a heating plate at 170°C for 1 hour.

[0078] (3) Lead iodide PbI2, formamidinium iodide FAI, lead bromide PbBr2, methyl ammonium bromide MABr, and cesium iodide CsI were dissolved in 1 mL of a mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio 4:1) at a molar ratio of 1.30:1.19:0.14:0.14:0.07, and then 1 mg of DT powder was added and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 2000 rpm for 10 s and 6000 rpm for 30 s. 20 s before the end of the program, 100 μL of chlorobenzene was dropped on the substrate and annealed at 100°C for 1 h.

[0079] The structure of the modified material used is:

[0080]

[0081] (4) Then 60 μL of 1 mg mL -1 The DT solution was dropped onto the perovskite film by spin coating process at 4000 rpm for 20 s.

[0082] (5) A hole transport layer solution (90 mg Spiro-OMeTAD, 39.5 μL tert-butylpyridine, 23 μL LiTFSI, 10 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film by spin coating, with the rotation speed controlled at 3000 rpm and the spin coating time at 30 s.

[0083] Finally, 100 nm of Au was deposited on the device film by vacuum evaporation.

[0084] Comparative Example 2

[0085] Preparation method of organic-inorganic hybrid CsFAMA perovskite solar cell without modification layer

[0086] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.

[0087] (2) Using a water bath deposition method, the treated FTO was immersed in a water bath deposition solution. The water bath deposition solution was a mixed solution of 50 mL deionized water, 625 μL 37.5% hydrochloric acid, 12.5 μL thioglycolic acid, 625 mg urea and 137.5 mg stannous chloride dihydrate. The water bath deposition solution was heated to 90°C for 4 hours, and then the FTO was washed with deionized water and placed on a heating plate at 170°C for 1 hour.

[0088] (3) Lead iodide PbI2, formamidinium iodide FAI, lead bromide PbBr2, methyl ammonium bromide MABr, and cesium iodide CsI were dissolved in a 1 mL mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio of 4:1) at a molar ratio of 1.30:1.19:0.14:0.14:0.07, and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 2000 rpm for 10 s and 6000 rpm for 30 s. 20 s before the end of the program, 100 μL of chlorobenzene was dropped on the substrate and annealed at 100°C for 1 h.

[0089] (4) A hole transport layer solution (90 mg Spiro-OMeTAD, 39.5 μL tert-butylpyridine, 23 μL LiTFSI, 10 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film by spin coating, with the rotation speed controlled at 3000 rpm and the spin coating time at 30 s.

[0090] Finally, 100 nm of Au was deposited on the device film by vacuum evaporation.

[0091] Figure 2 The JV curves of the DT-modified and unmodified CsFAMA perovskite solar cells are compared. The photoelectric conversion efficiency of the unmodified CsFAMA perovskite solar cell in Comparative Example 2 is: V oc 1.12V, J sc 23.74 mA cm -2 , FF is 76.73%, PCE is 20.35%, and the photoelectric conversion efficiency of the perovskite solar cell based on DT modification technology in Example 2 is V oc 1.17V, J sc 23.82 mA cm -2 , FF is 82.41%, PCE is 22.93%; the PCE of the perovskite solar cells before and after modification increased from 20.35% to 22.93%, an overall increase of 12.7%, with significant effects.

[0092] Example 3

[0093] Pure inorganic CsPbI2Br perovskite solar cell using 1,4-dithiane (DT) as a modified layer and preparation method thereof: The structure of the perovskite solar cell is:

[0094] FTO / SnO2 / CsPbI2Br-DT / DT / Spiro-OMeTAD / Au.

[0095] The preparation process of the above perovskite solar cell is as follows:

[0096] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.

[0097] (2) Using a water bath deposition method, the treated FTO was immersed in a water bath deposition solution. The water bath deposition solution was a mixed solution of 50 mL deionized water, 625 μL 37.5% hydrochloric acid, 12.5 μL thioglycolic acid, 625 mg urea and 137.5 mg stannous chloride dihydrate. The water bath deposition solution was heated to 90°C for 4 hours, and then the FTO was washed with deionized water and placed on a heating plate at 170°C for 1 hour.

[0098] (3) Lead iodide, lead bromide, cesium iodide and cesium bromide were dissolved in 1 mL of dimethyl sulfoxide organic solvent in a molar ratio of 1:1:2:0, and 1 mg of DT powder was added, and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 1500 rpm for 15 s and 3500 rpm for 30 s, and annealed at 200°C for 10 min.

[0099] The structure of the modified material used is:

[0100]

[0101] (4) Then 60 μL of 1 mg mL -1 The DT solution was dropped onto the perovskite film by spin coating process at 4000 rpm for 20 s.

[0102] (5) A hole transport layer solution (90 mg Spiro-OMeTAD, 39.5 μL tert-butylpyridine, 23 μL LiTFSI, 10 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film by spin coating, with the rotation speed controlled at 3000 rpm and the spin coating time at 30 s.

[0103] Finally, 100 nm of Au was deposited on the device film by vacuum evaporation.

[0104] Comparative Example 3

[0105] Preparation method of pure inorganic CsPbI2Br perovskite solar cell without modification layer:

[0106] The method adopts the preparation method of Example 3, except that the DT powder added in step (3) and the step (4) of spin-coating the DT solution are removed, and the remaining steps are consistent with Example 3, and finally a pure inorganic CsPbI2Br perovskite solar cell without a modification layer is obtained.

[0107] Figure 3Comparison of JV curves of DT-modified and unmodified perovskite solar cells. The photoelectric conversion efficiency of the unmodified perovskite solar cell in Comparative Example 3 is V oc 1.20V, J sc 14.97 mA cm -2 , FF is 68.58%, PCE is 12.34%, and the photoelectric conversion efficiency of the perovskite solar cell based on DT modification technology in Example 3 is V oc 1.25V, J sc 16.02 mA cm -2 , FF is 72.12%, and PCE is 14.41%. The PCE of the perovskite solar cell before and after modification increased from 12.34% to 14.41%, an overall increase of 16.77%, and the efficiency was significantly improved.

[0108] Example 4

[0109] Organic-inorganic FAPbI3 perovskite solar cell using 1,4-disulfide-2,5-diol as a modified layer and preparation method thereof: The structure of the perovskite solar cell is:

[0110] FTO / SnO2 / FAPbI3-DT / DT / Spiro-OMeTAD / Au. The preparation process of the above perovskite solar cell is:

[0111] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.

[0112] (2) Using a water bath deposition method, the treated FTO was immersed in a water bath deposition solution. The water bath deposition solution was a mixed solution of 50 mL deionized water, 625 μL 37.5% hydrochloric acid, 12.5 μL thioglycolic acid, 625 mg urea and 137.5 mg stannous chloride dihydrate. The water bath deposition solution was heated to 90°C for 4 hours, and then the FTO was washed with deionized water and placed on a heating plate at 170°C for 1 hour.

[0113] (3) Lead iodide PbI2, formamidinium iodide FAI, lead bromide PbBr2, methyl ammonium bromide MABr, and cesium iodide CsI were dissolved in a 1 mL mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio 8:1) at a molar ratio of 1:1:0:0:0, and then 1 mg of 1,4-dithio-2,5-diol powder was added and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 2000 rpm for 10 s and 6000 rpm for 30 s. 20 s before the end of the program, 100 μL of chlorobenzene was dropped on the substrate and annealed at 100°C for 1 h.

[0114] The structure of the modified material used is:

[0115]

[0116] (4) Then 60 μL of 1 mg mL -1 The 1,4-disulfide-2,5-diol solution was dropped onto the perovskite film by spin coating process at 4000 rpm for 20 s.

[0117] (5) A hole transport layer solution (90 mg Spiro-OMeTAD, 39.5 μL tert-butylpyridine, 23 μL LiTFSI, 10 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film by spin coating, with the rotation speed controlled at 3000 rpm and the spin coating time at 30 s.

[0118] Finally, 100 nm of Au was deposited on the device film by vacuum evaporation.

[0119] Comparative Example 4

[0120] Preparation method of FAPbI3 unmodified perovskite solar cells:

[0121] (1) FTO (fluorine-doped tin dioxide) was ultrasonically cleaned with deionized water, acetone, and ethanol for 30 min, respectively, and then surface treated with ozone UV for 20 min.

[0122] (2) Using a water bath deposition method, the treated FTO was immersed in a water bath deposition solution. The water bath deposition solution was a mixed solution of 50 mL deionized water, 625 μL 37.5% hydrochloric acid, 12.5 μL thioglycolic acid, 625 mg urea and 137.5 mg stannous chloride dihydrate. The water bath deposition solution was heated to 90°C for 4 hours, and then the FTO was washed with deionized water and placed on a heating plate at 170°C for 1 hour.

[0123] (3) Lead iodide PbI2, formamidinium iodide FAI, lead bromide PbBr2, methyl ammonium bromide MABr, and cesium iodide CsI were dissolved in a 1 mL mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide (volume ratio 8:1) at a molar ratio of 1:1:0:0:0, and stirred at 60°C overnight; a perovskite film was deposited on the electron transport layer by a continuous two-step spin coating process at 2000 rpm for 10 s and 6000 rpm for 30 s. 20 s before the end of the program, 100 μL of chlorobenzene was dropped on the substrate and annealed at 100°C for 1 h.

[0124] (4) A hole transport layer solution (90 mg Spiro-OMeTAD, 39.5 μL tert-butylpyridine, 23 μL LiTFSI, 10 μL Co(III)-TFSI dissolved in 1 mL chlorobenzene) was spin-coated onto the surface of the perovskite film by spin coating, with the rotation speed controlled at 3000 rpm and the spin coating time at 30 s.

[0125] Finally, 100 nm of Au was deposited on the device film by vacuum evaporation.

[0126] Figure 4 The JV curves of the unmodified perovskite solar cell based on 1,4-disulfide-2,5-diol modification are compared. The PCE of the unmodified perovskite solar cell in Comparative Example 1 is 22.07%, where V oc 1.17V, J sc 24.57 mA cm -2 , FF is 76.81%, and the photoelectric conversion efficiency PCE of the perovskite solar cell based on 1,4-disulfide-2,5-diol modification technology in Example 4 is 25.34%, wherein V oc 1.18V, J sc 26.63 mA cm -2 , FF is 80.96%; the PCE of the perovskite solar cells before and after modification increased from 22.07% to 25.34%, an overall increase of 14.82%, and the photoelectric conversion efficiency after modification reached more than 25%.

[0127] like Figure 5 As shown, the X-ray energy spectra of the Pb 4f orbitals of the two perovskite films with and without DT modification show that when the perovskite film is modified with DT, the zero-valent lead peak disappears significantly after modification, and the Pb 4f peak of the modified film shifts toward the low energy band direction, indicating that the use of DT modification effectively suppresses Pb defects.

[0128] like Figure 6As shown, the steady-state fluorescence spectra of the two perovskite films with and without DT modification show that the DT-modified perovskite has a stronger fluorescence response, indicating that the DT-modified perovskite film has fewer defects and reduces the non-radiative recombination of the film, resulting in higher open circuit voltage and fill factor in perovskite solar cell devices.

Claims

1. A method for modifying a perovskite layer with 1,4-dithiane and its derivatives, characterized in that: The perovskite layer is a layer of a perovskite solar cell. The perovskite layer is Cs x (FA, MA) 1−x PbI 3−y Br y Or all-inorganic perovskite CsPbI z Br 3-z One of the following, in which FA is CH(NH2)2 + , MA is CH3NH3 + , 0≤ x <0.1,0≤ y <0.6,0≤ z ≤3; This method uses 1,4-dithiane modifiers to passivate lead site defects on the surface and bulk of perovskite, forming passivation on the surface and grain boundaries of the perovskite to obtain a surface and bulk modified perovskite layer: The specific steps of this method are: (1) Adding 1,4-dithiane modifier to the perovskite precursor solution, spin coating and annealing the precursor solution to form a doped perovskite layer; the ratio of 1,4-dithiane modifier to perovskite precursor solution is (0.1-10) mg: 1 mL; The structural formula of the 1,4-dithiane modification is: ; (2) Spin coating the 1,4-dithiane modification solution on the doped perovskite layer at a spin coating speed of 4000 rpm for 20 s to obtain a modified perovskite layer; the concentration of the 1,4-dithiane modification solution is 1-5 mg mL -1 , the solvent used in the solution is isopropanol, ethanol or ethyl acetate; The perovskite layer is Cs x (FA,MA) 1−x PbI 3−y Br y When the molar ratio of lead iodide: methylammonium iodide: lead bromide: methylammonium bromide: cesium iodide in the precursor solution is 1-1.5: 1-1.5: 0-0.5: 0-0.5: 0-0.1; The perovskite layer is CsPbI z Br 3-z When the molar ratio of lead iodide: lead bromide: cesium iodide: cesium bromide in the precursor solution is 0-3: 0-3: 0-3: 0-3, and the ratio of lead iodide to lead bromide cannot be zero at the same time, and the ratio of cesium iodide to cesium bromide cannot be zero at the same time.

2. A method for preparing solar cells by modifying perovskite thin films with 1,4-dithiane and its derivatives, wherein the perovskite solar cell comprises a transparent conductive substrate, an electron transport layer, a modified perovskite layer, a hole transport layer, and a metal electrode, characterized in that: The specific steps of this method are as follows: (1) ultrasonically cleaning the transparent conductive substrate in different solvents; (2) after step (1), preparing an electron transport layer on the transparent conductive substrate by chemical bath deposition or thermal spraying; The electron transport layer is tin dioxide or titanium dioxide; (3) subjecting a transparent conductive substrate having an electron transport layer to a UV-ozone surface treatment to obtain a modified perovskite layer using the method of claim 1; (4) preparing a hole transport layer solution on the modified perovskite layer by spin coating; The hole transport layer solution comprises a hole transport material, an additive, and an organic solvent. The hole transport material is 2,2',7,7'-tetra[ N , N -bis(4-methoxyphenyl)amino]-9,9'-spirobifluorene; the additives are bis(trifluoromethane)sulfonyl imide, 4-tert-butylpyridine and tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridinium]cobalt tris(1,1,1-trifluoro- N -[(trifluoromethyl)sulfonyl]methanesulfonamide salt); the organic solvent is chlorobenzene or acetonitrile; (5) Depositing a metal electrode onto the hole transport layer by vacuum evaporation.

Citation Information

Patent Citations

  • Doped perovskite solar cell and preparation method thereof

    CN114141952A